Impacto del audiovisual en el desarrollo cultural y turístico: caso Aventureros cs6 - Duran Romero, Elsy Brigitte; Jaramillo Paredes, Segundo Yoneli (Machala : Universidad Técnica de Machala, 2025)
This research aims to analyze how the audiovisual project Aventureros CS6 contributes to the cultural strengthening and tourism promotion of rural parishes in the province of El Oro, Ecuador. Despite their rich cultural and natural heritage, these localities face limitations in resources, infrastructure, and promotion strategies, which have hindered their positioning as tourist destinations. Using a qualitative approach, the study applied techniques such as content analysis of the series, in-depth interviews with experts and institutional representatives, and focus groups with community leaders from the parishes involved. The results show that Aventureros CS6 effectively integrates visual and narrative elements that showcase tangible heritage (architecture, landscapes, historical infrastructure) and intangible heritage (music, dances, gastronomy, ancestral knowledge), generating an audiovisual discourse that strengthens local identity and fosters a sense of belonging. The project also contributes to building a coherent and attractive territorial brand, reinforcing community-based tourism and promoting sustainable development. It is concluded that such productions are strategic communication tools to give visibility to historically marginalized territories, boost the local economy, and encourage citizen participation in cultural and tourism management.
La presente investigación tiene como objetivo analizar cómo el proyecto audiovisual Aventureros CS6 aporta al fortalecimiento cultural y a la promoción turística de las parroquias rurales de la provincia de El Oro, Ecuador. Estas localidades, a pesar de su riqueza patrimonial y natural, enfrentan limitaciones en recursos, infraestructura y estrategias de promoción, lo que ha dificultado su posicionamiento como destinos turísticos. Bajo un enfoque cualitativo, se aplicaron técnicas como análisis de contenido de la serie, entrevistas en profundidad a expertos y representantes institucionales, y grupos focales con líderes comunitarios de las parroquias intervenidas. Los resultados muestran que Aventureros CS6 integra de manera efectiva elementos visuales y narrativos que rescatan el patrimonio tangible (arquitectura, paisajes, infraestructura histórica) e intangible (música, danzas, gastronomía, saberes ancestrales), generando un discurso audiovisual que refuerza la identidad local y fomenta el sentido de pertenencia. Asimismo, el proyecto contribuye a la construcción de una marca territorial coherente y atractiva, fortaleciendo el turismo comunitario y promoviendo un desarrollo sostenible. Se concluye que este tipo de producciones representan herramientas estratégicas de comunicación para visibilizar territorios históricamente relegados, dinamizar la economía local e incentivar la participación ciudadana en la gestión cultural y turística.
Keywords: COMUNICACIÓN; PATRIMONIO CULTURAL; TURISMO; AUDIOVISUAL